Identification of genes associated with tolerance in the C Cavendish banana selection, GCTCV 218, against Fusarium oxysporum f. sp. cubense ‘subtropical’ race 4 - Viljoen, Altus (University of Pretoria, 2013)
Thesis (PhD (Plant Pathology))--University of Pretoria, 2006.